Scanned Laser Pico Projection and Stokes-Mueller Matrix Imaging Polarimetry for Detecting Cancer Cells With Different Cytoskeletal Organizations and Metastatic Potencies - Yu-Jen Chang; Yu-Lung Lo; Wen-Tai Chiu; Chih-Ling Huang; Heng-Ai Chang; Quoc-Hung Phan (IEEE Photonics Journal, 2018)
The scanned laser pico-projection (SLPP) method and Stokes–Mueller matrix polarimetry technique are used to distinguish cancer cells with different cytoskeletal organizations and metastatic potencies. The speckle contrast of human bone osteosarcoma cancer cells (U2OS) with different cytoskeletal drug treatments is measured by the SLPP method. The results show that the contrast is directly related to the organization of the microtubules and actin fibers. The Stokes–Mueller matrix polaimetry technique is employed to measure polarization parameters of the same samples. The measurement results are found to be consistent with those obtained using the SLPP method. Finally, the Stokes–Mueller matrix polaimetry technique is used to extract the polarization parameters of cell-pairs with different metastatic potencies. It is shown that the extracted value of the linear phase retardance (β) is particularly sensitive to the organization of the microtubules and actin fibers. Furthermore, the linear phase retardance (β) and depolarization index (Δ) are both sensitive to the metastatic potency of the cancer cells. In general, both techniques provide a rapid, noninvasive and label-free approach for distinguishing cancer cells with different cytoskeleton organizations and metastatic potentials, and are thus of significant benefit in evaluating the malignancy of cancer cells.